Analysis of Anti-seepage Effect of Masonry Gravity Dam Repaired by Geomembrane - WANG Libo; CEN Weijun; ZHENG Changhai (Renmin Zhujiang)
In view of the seepage of the dam body and dam foundation of a dangerous masonry gravity dam,this paper puts forward the seepage repair scheme of laying geomembrane on the dam surface and strengthening the curtain of the dam foundation,calculates the seepage field of the dam under multiple working conditions by the finite element method for obtaining the distribution of the equal head line,the height of the seepage line,the seepage gradient and the seepage flow of the dam,and emphatically demonstrates and analyzes the anti-seepage effect of geomembrane and curtain.The results show that:The geomembrane on the upstream face of the dam can significantly reduce the water head,the position of the dam seepage line after laying with the geomembrane is low,and the seepage flow of the dam is small.The curtain after reinforcement of dam foundation also has a good anti-seepage effect,which effectively limits the seepage of dam foundation,and the seepage gradient of curtain is smaller than the allowable gradient.Therefore,it is reasonable and feasible to use geomembrane combined with curtain reinforcement to repair the seepage of masonry gravity dam.